GOVERNMENT POLICY ON PROVISION OF FACILITIES AND INFRASTRUCTURE PUBLIC SPORTS IN PATI REGENCY - Putra, Ponda Kusuma; Sulaiman, Sulaiman; Hartono, Mugiyo (Journal of Physical Education and Sports, 2020)
This study aims to analyze planning in the provision of sports facilities and infrastructure, analyze the availability of sports facilities and infrastructure, analyze the use of sports facilities and infrastructure, analyze the management of sports facilities and infrastructure, analyze supporting factors and inhibitors of public sports facilities and infrastructure in Pati Regency. This study uses an integrative descriptive qualitative approach. The results study show that planning regarding the availability of sports facilities and infrastructure in the Pati Regency is already there but has not been appropriately realized, due to constraints by the budgetary funds for the sports sector. The availability of sports facilities and infrastructure is still concentrated in the center of Pati Regency, the number in the category is lacking, and the quality does not meet the standards. Utilization of sports facilities and infrastructure has not been carried out to the fullest, because sports facilities and infrastructure are still used for non-sporting purposes. The management of sports facilities and infrastructure has not been carried out optimally; as a result, the facilities and sports infrastructure are in poor condition. Supporting factors are Pati Regency already has a Regional Regulation on Sport as a strong legal basis for providing policies on the provision of sports facilities and infrastructure, and inhibiting factors include limited budget funds, which are given by the government for sports.